A homozygous variant in G6PC in a Vietnamese patient with glycogen storage disease type Ia - Thu, Nguyen Huu Hong; Thi Khanh Ly, Nguyen; Thuy Duong, Nguyen (Vietnam Journal of Biotechnology, 2022)
Glycogen storage diseases (GSDs) are rare inherited metabolic disorders characterized by the absence of required enzymes for the glycogen degradation metabolism. GSD can be divided into more than 12 types based on enzyme deficiency and affected tissues, in which glycogen storage disease type Ia (GSD1a or von Gierke disease) is a liver-affecting form. GSD1a is an autosomal recessive inherited disease caused by mutations in the G6PC gene on chromosome 17q21. The present study reports a Vietnamese family with a 6-month-old male patient diagnosed with type Ia glycogen storage disease. A homozygous variant in the G6PC gene (NM_000151.3: c.518T>C; p.L173P) was detected in the proband using a comprehensive glycogen storage disease panel. This variant has been previously reported in ClinVar (Accession ClinVar: VCV000640818.3). The segregation of the variant was confirmed in ten people of a 3-generation family using Sanger sequencing. The results showed both parents were heterozygous for the variant. In addition, the variant c.518T>C in the G6PC gene was predicted to be deleterious using in silico prediction tools (SIFT, PolyPhen-2, Proven, REVEL, and MutPred2). Our results could help doctors decide on appropriate treatment and diet for the disease. Moreover, the study is also a contribution to molecular studies on GSD1a.